KMT-2018-BLG-0029LB: A VERY LOW MASS-RATIO Spitzer MICROLENS PLANET - Andrew Gould; 류윤현; Sebastiano Calchi Novati; Weicheng Zang; Michael D. Albrow; 정선주; CHEONGHOHAN; 황규하(한국천문연구원; 정연길(한국천문연구원; 신인구(한국천문연구원; Yossi Shvartzvald; Jennifer C. Yee; et al. (Journal of the Korean Astronomical Society, 53(1), 2020)
At q = 1.81+/-0.20*10^{-5}, KMT-2018-BLG-0029Lb has the lowest planet-host mass ratio q of any microlensing planet to date by more than a factor of two. Hence, it is the first planet that probes below the apparent "pile-up" at q = 5-10*10^{-5}. The event was observed by Spitzer, yielding a microlens-parallax pi_E measurement. Combined with a measurement of the Einstein radius theta_E from finite-source effects during the caustic crossings, these measurements imply masses of the host M_host = 1.14+0.10-0.12 M_sun and planet M_planet = 7.59+0.75-0.69 M_Earth, system distance D_L = 3.38+0.22-0.26 kpc and projected separation a_p = 4.27+0.21-0.23 au. The blended light, which is substantially brighter than the microlensed source, is plausibly due to the lens and could be observed at high resolution immediately. KCI Citation Count: 19